2013
DOI: 10.7860/jcdr/2013/5726.2958
|View full text |Cite
|
Sign up to set email alerts
|

Self Care Activities, Diabetic Distress and other Factors which Affected the Glycaemic Control in a Tertiary Care Teaching Hospital in South India

Abstract: Background: Interventions which were made to promote a better self-management have produced improvements in the glycaemic control in patients with Diabetes mellitus. An improved glycaemic control is known to prevent the long term complications.Method: This study was conducted at the Dr. Pinnamaneni Siddhartha Institute of Medical Sciences and Research Foundation, which is a rural tertiary health care centre. 546 patients were included in our study and they were assessed for the glycaemic control (HbA1c), diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
6
9
3
Order By: Relevance
“…We also found that medication adherence exhibited the highest adherence value (6.3 d), followed by dieting (4.9 d), exercising (3.4 d), and blood glucose self-monitoring (2.8 d). These results agree with other studies' findings (Kang & Gu, 2012;Lee & Park, 2014;Osborn, Mayberry, & Kim, 2016;Sasi et al, 2013), which showed that type 2 diabetes patients exhibited the greatest values for medication adherence and relatively low adherence values for dieting, exercising, and blood glucose self-monitoring. The high value for medication adherence may be related to the relatively simple requirement to take a specific medication dose at the scheduled time; however, dieting, exercising, and blood glucose self-monitoring require more extensive habitual changes that are relatively difficult to perform (Lee & Park, 2014).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that medication adherence exhibited the highest adherence value (6.3 d), followed by dieting (4.9 d), exercising (3.4 d), and blood glucose self-monitoring (2.8 d). These results agree with other studies' findings (Kang & Gu, 2012;Lee & Park, 2014;Osborn, Mayberry, & Kim, 2016;Sasi et al, 2013), which showed that type 2 diabetes patients exhibited the greatest values for medication adherence and relatively low adherence values for dieting, exercising, and blood glucose self-monitoring. The high value for medication adherence may be related to the relatively simple requirement to take a specific medication dose at the scheduled time; however, dieting, exercising, and blood glucose self-monitoring require more extensive habitual changes that are relatively difficult to perform (Lee & Park, 2014).…”
Section: Resultssupporting
confidence: 92%
“…The high value for medication adherence may be related to the relatively simple requirement to take a specific medication dose at the scheduled time; however, dieting, exercising, and blood glucose self-monitoring require more extensive habitual changes that are relatively difficult to perform (Lee & Park, 2014). Furthermore, we only found that medication adherence was significantly associated with glycaemic control, whereas previous studies have found significant differences in glycaemic control according to exercise and diet (Kang & Gu, 2012); medication and exercise (Osborn et al, 2016); and medication, exercise, and diet (Sasi et al, 2013). These study-specific differences are presumably related to the use of different tools to measure self-care behaviours.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Jordon’s study (2010) Jordon found a weak correlation with age. In the study of Sasi Sekhar et al (2013), gender made a significant difference. Weak glycemic control was more prevalent among women.…”
Section: Discussionmentioning
confidence: 89%
“…The average A1c values of the group aged 36–49 years were significantly lower than the other groups. In the study of Sasi Sekhar et al (2013), a relation was found between age and A1c. Jordon’s study (2010) Jordon found a weak correlation with age.…”
Section: Discussionmentioning
confidence: 95%